Ruiz Triana,Jimmy Rodolfo(2023)EFECTO DE LA MACERACIÓN TERMICA DEL CACAO CCN-51 (Theobroma Cacao L.) EN LAS CARACTERÍSTICAS ORGANOLÉPTICAS Y COLORIMÉTRICAS DE UNA BEBIDA ALCOHÓLICA.Quevedo.UTEQ.101p. - Ruiz Triana , Jimmy Rodolfo (2023)
Maceration is a process where certain substances soluble in the liquid are extracted from a solid; In the chemical industry, this method is known as extraction, while in food manufacturing, the term maceration is used. The objective was to evaluate the effect of thermal maceration of cocoa CCN-51 (Theobroma Cacao L) on the sensory and colorimetric characteristics of an alcoholic beverage. To obtain the experimental responses, three factors corresponding to a 2n (A*B*C) design were combined, with 2 levels each and 3 repetitions; where A represents the percentage of cocoa beans used (15 - 20%), B the maceration temperature (55 - 65 °C), the maceration time in all treatments was 5 minutes and a size of the experimental unit of 2 L of tridistilled alcohol of 85 °GL and C the dilution level of the final drink (27-37 °GL). The L*a*b* color characteristics were studied according to the method recommended by the Office Internationale de la Vigne et du Vin (OIV). In sensometry, color tonality, limpidity, aroma, flavor, impression of the liquor and acceptability were evaluated. The experimental responses were evaluated in a free software in which the non-parametric test of Fredman and Holm was applied, prior to demonstrating that the data were not normally distributed. In conclusion, the colorimetry did not present significant differences between treatments, in contrast, the best treatment was determined based on the sensory evaluation a1b0c1, whose almond percentage was 20%, applied temperature 55 °C and diluted at 37 °GL, having a light amber hue, and this treatment had a value of L* 76.3, a* 5.96 and b*21.51.